P1832 T1 mapping and echo-global longitudinal strain are early markers of cardiac involvement in patients with fabry disease. (17th January 2020) - Gatterer, C; Beitzke, D; Bartko, P E; Schneider, M; Binder, T; Hengstenberg, C; Bergler-Klein, J; Sunder-Plassmann, G; Mundigler, G; Graf, S
Abstract: OnBehalf: Constantin Gatterer Introduction: Fabry disease (FD) is one of the most common lysosomal storage diseases caused by deficiency of Alpha-Galactosidase A and accumulation of glycosphingolipids in all cells containing lysosomes. Cardiac involvement is characterized by left ventricular hypertrophy, conduction abnormalities and myocardial fibrosis with consecutive cardiomyopathy in late stages. Purpose: As the detection of early signs of cardiac involvement is crucial for the initiation of enzyme replacement therapy (ERT) or Chaperon therapy, we intended to find early imaging markers. Methods: Cardiac MRI (CMR) including Late Gadolinium Enhancement (LGE), representing fibrosis, and T1-mapping as well as echocardiography with measurement of global longitudinal strain (GLS) were done as part of the regular check-ups for patients with FD. Results: The study cohort of 30 FD patients (20-69 years, 53% women) in different stages of disease showed low GLS values already at the time of baseline echocardiography (mean: -17, 22%), correlating with the amount of LGE (r = 0, 73; p = 0, 003) and ejection fraction measured by CMR (CMR-EF; r=-0, 74; p = 0, 002). After an average follow-up of 39 months (STD 18), GLS values were significantly declined (-15, 51 %; p = 0, 009) and correlated with T1 times (r = 0, 7; p = 0, 04), while LGE and CMR-EF did not significantly change compared to baseline. Baseline T1 times correlated negatively with the reduction of GLS (r=-0, 7; p = 0, 003), while LGE and CMR-EF showed no correlation with the course of GLS. ERT appeared to have no influence on the extend of GLS reduction. Conclusion: Low native CMR T1 times, indicating sphingolipid accumulation in the myocardium, seem to represent the beginning of cardiac involvement in FD and might predict the course of GLS. GLS is a sensitive parameter for early detection of cardiac manifestation and disease progression, while LGE and CMR-EF could not recognize slight deterioration of left ventricular function.